An evaluation model for digital libraries' user interfaces using fuzzy AHP. Issue 1 (28th January 2014) - Lai, Chin-Feng; Chiu, Po-Sheng; Huang, Yueh-Min; Chen, Tzung-Shi; Huang, Tien-Chi
Abstract : Purpose: – The aim of this paper is to improve the service quality of digital libraries (DLs) through an evaluation model for DLs' user interfaces. This evaluation model can provide a useful reference for existing DLs or relevant research. Design/methodology/approach: – Relevant literature was synthesized, an evaluation framework was established, and the Fuzzy AHP was employed to investigate the evaluation model for DLs' user interfaces, obtain the relative weights for the importance of the evaluation criteria, and establish the priority ranking for the criteria of DLs' user interfaces. Findings: – The top five criteria are ease of use, searching, language, presentation, and design, respectively. For users, an interface should be intuitive. Good interface presentation and design are critical when users evaluate a digital library. Practical implications: – All of the students, teachers and experts considered that the presentation and design of DL user interfaces were what users had had contact with in the very beginning, and they were critical influential factors in DL user interfaces. Furthermore, ease-of-use and searching were fundamental interface functions, as well as important evaluation criteria. Interfaces should also provide interactive functions to improve interaction, while tailor-made services should be taken into account to establish an excellent interface in order to meet each user's need. Originality/value: – The evaluation model for DLs' user interfaces employed in this study will help developers of DL user interfaces discover the criteria that they should aim for as a reference, perform comprehensive criteria evaluation according to their actual needs, and employ top criteria for evaluation.